H Hubungan Pendekatan Health Belief Model (HBM) Terhadap Minat Masyarakat Pada Vaksinasi Booster Covid-19 di Kelurahan Tumbang Miri - Pebrianti, Pebrianti; Yuwindry, Iwan; Herawati, Anita (LPPM Universitas Sari Mulia, 2023)
Background: The Covid-19 pandemic has infected millions of people and caused up to 143,685 deaths in Indonesia. One of the most promising Covid-19 prevention strategies is vaccination. Although clinical investigations have proven the safety of Booster doses, public rejection or hesitation due to effectiveness and safety reasons is still a major problem in the Covid-19 Booster vaccination program. Objective: To determine the relationship of the Health Belief Model (HBM) approach to public interest in Covid-19 Booster vaccination in Tumbang Miri Village. Methods: Quantitative research with a cross-sectional approach. Sampling with purposive sampling technique. The number of samples obtained was 81 respondents. Univariate data analysis for respondent characteristics and bivariate analysis of Chi-square statistical tests to determine the relationship between the Health Belief Model and acceptance of Booster Covid-19 vaccination. Sampling was carried out for one month, starting from June 2023. Results: Perceived susceptibility had an association with vaccine acceptance (0.008 < 0.05), perceived severity had no association with vaccine acceptance (0.225, 0.137 and 0.913 > 0.05), perceived benefit had an association with vaccine acceptance (0.009 and 0.000 < 0.05), perceived barriers had no association with vaccine acceptance (0.272, 0.471 and 0.913 > 0.05), trigger to act had an association with vaccine acceptance (0.032 and 0.000 < 0.05). Conclusion: Perceived susceptibility, perceived benefits, and triggers to act have a relationship with the acceptance of Booster Covid-19 vaccination in the community of Tumbang Miri Village.